The politics of terrorism and counterterrorism in Bangladesh - Parvez, Saimum; Rahman, Mohammad Sajjadur (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book examines contemporary issues and debates of terrorism in Bangladesh, including national and transnational terrorist outfits operating within the country, their narratives and counternarratives, ideologues, women and the youth, media representation, counterterrorism laws, and challenges. Bangladesh is a fascinating and often paradoxical case study for terrorism studies. The book examines major terrorist groups in contemporary Bangladesh, their international connections, narratives, and a case study of an influential ideologue who encouraged some Bangladeshis to engage in violence. The chapters discuss how women and youth play a role in Bangladeshi terrorism, how the Internet is used for recruiting terrorists, the discourses of the media and state regarding terrorism, as well as the politics of law and counterterrorism initiatives, including critically evaluating non-state actors and government responses. In addition to providing an up-to-date analysis of terrorism and counterterrorism in Bangladesh, this book offers a balanced and unbiased perspective on this subject. It will appeal to academics and international policymakers who are researching violence and extremism in South Asia"--
Keywords: Terrorism -- Bangladesh; Terrorism -- Bangladesh -- Prevention; Bangladesh -- Politics and government -- 1971-; SOCIAL SCIENCE / Ethnic Studies / General